Advancing the K-12 reform from the ground a case study in the Philippines. - Oracion, Carmela; Naidu, Vignesh Louis; Ng,Jasmine; Reyes, Vicente Jr (ADB sustainable development working paper series, 2020)
This paper describes the implementation of the Certificate in Educational Studies in Leadership (CESL) in the Philippines as a professional development initiative delivered in a customized blended learning mode.